2006
DOI: 10.1007/s00415-006-0269-x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cerebral angiopathy

Abstract: Reversible cerebral angiopathy (RCA) is responsible for disabling headache and potential stroke complications. Most patients respond poorly to analgesics. We describe four patients with typical RCA whose headache rapidly disappeared after IV nimodipine treatment was initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 12 publications
0
25
1
2
Order By: Relevance
“…While on nimodipine, four patients had transient ischemic attack and one patient had multiple cerebral infarcts. Contrasting with the previously published experience of positive effects of nimodipine, these results suggest that nimodipine needs to be evaluated in a placebo-controlled study [32,33].…”
Section: Treatmentcontrasting
confidence: 82%
“…While on nimodipine, four patients had transient ischemic attack and one patient had multiple cerebral infarcts. Contrasting with the previously published experience of positive effects of nimodipine, these results suggest that nimodipine needs to be evaluated in a placebo-controlled study [32,33].…”
Section: Treatmentcontrasting
confidence: 82%
“…However, it is not clear how lesions can be prevented or whether vasoconstriction monitoring has any use. Although some case series suggest benefit with nimodipine, 19 other studies have not shown therapeutic benefit with calcium-channel blocker therapy. 4,16 The risk of developing new brain lesions seems substantial (5 of 19 patients) in patients with ICH and relatively low (5 of 56 patients) in those with cSAH on initial imaging.…”
Section: Strokementioning
confidence: 99%
“…In a few randomized, controlled studies of approximately 8-to 16-weeks' duration, oral nimodipine 120 mg daily in divided doses reduced the frequency and possibly the severity and duration of migraine attacks in patients with classic or common migraine (140)(141)(142)(143)(144). In general, benefit was observed within 1-2 months after beginning of treatment (141,(145)(146)(147)(148)(149).…”
Section: Migrainementioning
confidence: 88%